Effect of resource conservation practices on performance of Yellow sarson (Brassica rapa L.) grown on sandy loam soil - SINGH, SAMAR PAL; MAHAPATRA, B. S.; YADAV, VIMAL RAJ; SRIVASTAVA, ASHUTOSH (Journal of Soil and Water Conservation, 2019)
Field experiments were conducted for two consecutive rabi seasons during 2014-15 and 2015-16 at Norman E. Borlaug Crop Research Centre of G.B. Pant University of Agriculture and Technology, Pantnagar to evaluate growth and yield parameters yellow sarson (Brassica rapa L.) affected by different irrigation levels, planting methods and mulching. Significantly higher numbers of secondary branches per plant and dry matter accumulation in leaves and stem were reported at 1.2 IW/CPE ratio over 0.6 and 0.3 IW/ CPE ratio in both the years. Sarson crop irrigated at 1.2 IW/CPE ratio, seed yield increased significantly at as compared to 0.9 IW/CPE ratio, 0.6 IW/CPE ratio and 0.3 IW/CPE ratio in both the years, while found at par with 0.9 IW/CPE ratio in first year. In both the years, yellow sarson planted on raised bed produced 11.5 and 7.1% higher seed yield over flat bed planting method, respectively. Mulching had significant influenced on seed yield. In both years, application of rice mulch recorded 11.7 and 12.3 % more seed yield than no mulch, respectively.